Co-flowering plants support diverse pollinator populations and facilitate pollinator visitation to sweet cherry crops - Gilpin, Amy-Marie; O'Brien, Corey; Kobel, Conrad; Brettell, Laura E.; Cook, James M.; Power, Sally A. (Basic and applied ecology, 2022)
Many food crops depend on animal pollination to set fruit. In light of pollinator declines there is growing recognition of the need for agro-ecosystems that can sustain wild pollinator populations, ensuring fruit production and pollinator conservation into the future. One method of supporting resident wild pollinator populations within agricultural landscapes is to encourage and maintain floral diversity. However, pollinator visitation to crop plants can be affected either positively (facilitation) or negatively (competition) by the presence of co-flowering plants. The strength and direction of the facilitative/competitive relationship is driven by multiple factors, including floral abundance and the degree of overlap in pollinator visitation networks. We sought to determine how plant-pollinator networks, within and surrounding sweet cherry (Prunus avium) orchards, change across key time points during the cherry flowering season, in three growing regions in Australia. We found significant overlap in the suite of flower visitors, with seven taxa (including native bees, flies, hoverflies and introduced honey bees, Apis mellifera) observed visiting cherry and other co-flowering species within the orchard and/or the wider surrounding matrix. We found evidence of pollinator facilitation with significantly more total cherry flower visits with increasing percent cover of co-flowering plants within the wider landscape matrix and increased visitation to cherry by honey bees with increasing co-flowering plant richness within the orchard. During the cherry flowering period there was a significant positive relationship between pollinator richness on cherry and pollinator richness on co-flowering plants within the orchard and the area of native vegetation surrounding orchards. Outside of the crop flowering season, co-flowering plants within the orchard and wider landscape matrix supported the same pollinator taxa that were recorded visiting cherry when the crop was flowering. This shows wild plants help support the pollinators important to crop pollination, outside of the crop flowering season, highlighting the role of co-flowering plants within pollinator-dependent cropping systems. [Display omitted]